Saprotrophic proteomes of biotypes of the witches' broom pathogen Moniliophthora perniciosa. Issue 9 (September 2017) - Pierre, Sandra; Griffith, Gareth W.; Morphew, Russell M.; Mur, Luis A.J.; Scott, Ian M.
Abstract: Nine geographically diverse Moniliophthora perniciosa (witches' broom disease pathogen) isolates were cultured in vitro . They included six C-biotypes differing in virulence on cacao ( Theobroma cacao ), two S-biotypes (solanaceous hosts), and an L-biotype (liana hosts). Mycelial growth rates and morphologies differed considerably, but no characters were observed to correlate with virulence or biotype. In plant inoculations using basidiospores, one C-biotype caused symptoms on tomato (an S-biotype host), adding to evidence of limited host adaptation in these biotypes. Mycelial proteomes were analysed by two-dimensional gel electrophoresis (2-DE), and 619 gel spots were indexed on all replicate gels of at least one strain. Multivariate analysis of gel spots discriminated the L-biotype, but not the S-biotypes, from the remaining strains. The proteomic similarity of the S- and C-biotypes is consistent with their reported lack of phylogenetic distinction. Sequences from tandem mass spectrometry of tryptic peptides from major 2-DE spots were matched with Moniliophthora genome and transcript sequences on NCBI and WBD Transcriptome Atlas databases. Protein-spot identifications indicated that M. perniciosa saprotrophic mycelial proteomes expressed functions potentially connected with a 'virulence life-style', including peroxiredoxin, heat-shock proteins, nitrilase, formate dehydrogenase, a prominent complement of aldo-keto reductases, mannitol-1-phosphate dehydrogenase, and central metabolism enzymes with proposed pathogenesis functions.